THE PROBLEM OF THE CRISIS OF SPIRITUALITY IN THE CONTEXT OF NEW CIVILIZATION CHALLENGES - Chenbai, Natalia (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2023)
Introduction. The beginning of the new millennium can be defined as the time summing up the entire previous history. We got new opportunities to communicate, discuss our interests on an equal footing, and outline common goals while preserving our individual identities and our own belief systems. It is recognized that the development of civilization should take place through a progressive approach to spiritual growth. But at the beginning of the 21st century, the symptoms of the spiritual backwardness of civilizations became threatening, and therefore the problem of overcoming the spiritual crisis came to the fore. The aim and tasks are to identify the causes and features of manifestations of the crisis of spirituality on a global scale. Research methods. This research’s theoretical and methodological basis is the works of S. Huntington, O. Spengler, and A. Toynbee. The sociocultural approach, as well as the principles of historicism and systematicity, are important methodological tools for the study. Research results. Spirituality presupposes the individual’s choice of his own life path and forms a tolerant attitude towards other people. It is recognized that social changes over time lead to the transformation of a person’s spiritual values. And therefore, one of the current important tasks is to live without conflicts with others. Discussion. Humanity is forced to develop new strategies for human socialization. In the future, the acceleration of exchanging material and spiritual values between different civilizations and cultures is predicted. The partnership of civilizations is recognized as the most promising scenario for the further development of the world. Conclusion. New challenges intensify the existing differences in the world community. Existing problems require long-term cooperation for their solution, which requires a preliminary revival of humanity’s spirituality.